(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
Acute intestinal obstruction (AIO) remains one of the leading emergencies in abdominal surgery, associated with significant morbidity and mortality. In patients with concomitant diffuse liver diseases (DLD), including chronic hepatitis and cirrhosis, the prognosis worsens due to impaired detoxification, protein-synthesizing and coagulation functions of the liver. These patients are at increased risk of severe infectious and thromboembolic complications. Therefore, the implementation of hepatoprotective therapy during the perioperative period is of particular importance, as it may improve postoperative recovery, reduce adverse outcomes, and enhance overall survival.